A clinico-epidemiological study of macular amyloidosis from North India - Anshu Bandhlish; Asok Aggarwal; Ravinder V Koranne (Wolters Kluwer Medknow Publications, 2012)
Background : Macular amyloidosis (MA) is the most subtle form of cutaneous amyloidosis, characterized by brownish macules in a rippled pattern, distributed predominantly over the trunk and extremities. MA has a high incidence in Asia, Middle East, and South America. Its etiology has yet to be fully elucidated though various risk factors such as sex, race, genetic predisposition, exposure to sunlight, atopy and friction and even auto-immunity have been implicated. Aim: This study attempts to evaluate the epidemiology and risk factors in the etiology of MA. Materials and Methods: Clinical history and risk factors of 50 patients with a clinical diagnosis of MA were evaluated. Skin biopsies of 26 randomly selected patients were studied for the deposition of amyloid. Results: We observed a characteristic female preponderance (88%) with a female to male ratio of 7.3:1, with a mean age of onset of MA being earlier in females. Upper back was involved in 80% of patients and sun-exposed sites were involved in 64% cases. Incidence of MA was high in patients with skin phototype III. Role of friction was inconclusive . Lymphohistiocytic infiltrate in the dermis and in perivascular distribution was seen in almost all the histopathology sections studied. Focal disruption of basal layer with pigmentary incontinence was present in a small number of patients. Amyloid deposits could be detected better with Congo red staining viewed under polarized light . Conclusion: Lack of clear-cut etiological factors makes it difficult to suggest a reasonable therapeutic modality. Histopathology is not specific and amyloid deposits can be demonstrated only in a small number of patients. For want of the requisite information on the natural course and definitive etiology, the disease MA remains an enigma and a source of concern for the suffering patients.